Pengaruh Aplikasi Siskeudes dan SPI terhadap Kualitas Laporan Keuangan Desa dengan Kompetensi SDM sebagai Variabel Pemoderasi - Tunya, Maria Grasella; Riharjo, Ikhsan Budi; Ardini, Lilis (Jurnal Samudra Ekonomi dan Bisnis, 2023)
The research aims to examine the influence of the use of village financial system applications and internal control systems on the quality of village financial reports, with human resource competency as a moderating variable. This quantitative research uses a moderated regression data analysis method. The results show that the use of village financial system applications and internal control systems is proven to have a positive effect on the quality of village financial reports, while the human resource competency obtained does not moderate the influence of the use of village financial system applications on the quality of village financial reports or the influence of the internal control system on the quality of village financial reports. The recommendation given is that improving the quality of human resources using the system is a point that village officials need to pay attention to.